2012
DOI: 10.1021/bm3012715
|View full text |Cite
|
Sign up to set email alerts
|

Phenylboronic Acid-Based Complex Micelles with Enhanced Glucose-Responsiveness at Physiological pH by Complexation with Glycopolymer

Abstract: Polymeric nanoparticles with glucose-responsiveness under physiological conditions are of great interests in developing drug delivery system for the treatment of diabetes. Herein, glucose-responsive complex micelles were prepared by self-assembly of a phenylboronic acid-contained block copolymer PEG-b-P(AA-co-APBA) and a glycopolymer P(AA-co-AGA) based on the covalent complexation between phenylboronic acid and glycosyl. The formation of the complex micelles with a P(AA-co-APBA)/P(AA-co-AGA) core and a PEG she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 41 publications
2
136
0
Order By: Relevance
“…Polymers based on PBA retain this glucose sensitivity; further, they generally possess high stability and can be structurally very versatile, and thus can be used to develop a broad range of systems. 17,18 Unfortunately, glucose-sensitive PBA polymers face a number of challenges, including having shown some cytotoxicity. The pKa of PBA (~9.0) is much higher than the physiological pH, and thus, in the body, a PBA homopolymer is largely unionized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers based on PBA retain this glucose sensitivity; further, they generally possess high stability and can be structurally very versatile, and thus can be used to develop a broad range of systems. 17,18 Unfortunately, glucose-sensitive PBA polymers face a number of challenges, including having shown some cytotoxicity. The pKa of PBA (~9.0) is much higher than the physiological pH, and thus, in the body, a PBA homopolymer is largely unionized.…”
Section: Introductionmentioning
confidence: 99%
“…The pKa of PBA (~9.0) is much higher than the physiological pH, and thus, in the body, a PBA homopolymer is largely unionized. 18 This renders it insoluble, and therefore it has only a minimal interaction with glucose in solution, limiting its ability to respond to changes in the concentration of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…34 This demonstrated that the introduction of nitrogen atom adjacent the boronic acid via formation of imine bond by aldehyde and amino group induced most of the neutral R-B(OH) 2 being transformed into the anionic R-B(OH) 3 À which had a stronger tendency to combine 1,2-diols. 23 When CAPE was further added into the 1-BA/2-FPBA system, the peak of the N-B coordinated tetrahedral boron moved from 8.9 ppm to 14.4 ppm, indicating the formation of cyclic boronate. 34 The N-B coordination was favourable for the formation of boronate, and in return the boronate also could promote the N-B coordination by raising the electrophilicity, or the Lewis acidity, of the boron atom.…”
Section: Characterizationsmentioning
confidence: 98%
“…[23][24][25][26][27][28] Based on these properties, pH and GSHresponsive releases of CAPE were studied. The pH and GSHsensitive dissociation of the micelles can also be applied in a general manner to other 1,2-diol containing drugs, presenting a promising utility in biomedical eld.…”
Section: 12mentioning
confidence: 99%
“…This delivery is also more resistant to enzymatic degradation, denaturation and immune recognition, which are major problems faced by insulin delivered through non-invasive administration. To design closedloop smart insulin delivery, insulin is embedded in a polymeric matrix that contains glucose-sensitive molecules, such as phenylboronic acid [56], glucose oxidase [55], and glucose binding proteins, mainly lectins [57] such as concanavalin A that possesses four glucose binding sites.…”
Section: Nascent Nanotechnology-based Approaches For Controlled Delivmentioning
confidence: 99%